When authors become inventors: An empirical analysis on patent-paper pairs in medical research - Arianna Martinelli; Elena Romito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
This paper investigates the effect of patenting on follow-on knowledge in cancer research. Using a difference-in-difference approach on an original dataset of patent-paper-pairs we are able to estimate the causal effect of the granting of a patent on scientic development in the same domain. Furthermore, we disentangle between private companies and universities in order to assess whether patenting impacts differently on the two groups. In addition, we study to which extend the degree of applicability of an innovation is further affects the relation. To address these issues we build a novel dataset matching patent data (retrieved from USPTO) and publication data (retrieved from Thompson-Web of Science). Results show that patenting reduces the rate of citations of the paired publication indicating a decrease of related scientic activity only in case the citing agent belongs to a public institution. In addition, the the more invention is applied, the weaker is the negative effect. This paper makes a contribution to the debate on IPR and economics of science.
Keywords: O30; O31; O34; 330; IPRs; Patent; Scientific publications; Applicability